Jens Andermann. Tierras en trance: arte y naturaleza después del paisaje. Santiago de Chile: Metales Pesados, 2018. - Campisi, Nicolás (Badebec, 2020)
Jens Andermann. Tierras en trance: arte y naturaleza después del paisaje. Santiago de Chile: Metales Pesados, 2018.